Analysis of the influence of CAR, NPF, FDR AND BOPO on the financial performance (ROA) of banking in Indonesia - Vina Wijayanti; Nursiam (Indonesian Journal of Islamic Economics Research, 2024)
This article analyzes the influence of CAR, NPF, FDR and BOPO on banking financial performance (ROA) in Indonesia, which is the aim of this research. The sample selection method uses a purposive sampling technique at Sharia Commercial Banks registered with Bank Indonesia (BI) for the 2017-2022 period. The sample in this study consisted of 10 companies with a total sample data of 58. The data analysis technique used was multiple linear regression with the help of SPSS version 25. The results of the study showed that the NPF variable had an effect on financial performance (ROA), while CAR, FDR and BOPO did not. influence on financial performance (ROA). The selection of research objects at Sharia Commercial Banks resulted in limitations in the number of samples in this research. Apart from that, the independent variables in this study can only explain 19.8% of the independent variables.